The impact of Tai Chi on emotional regulation efficacy and subjective wellbeing in the elderly and the mediating mechanism - Wang, Shiguang; Huang, Yongchao; Si, Xuyan; Zhang, Huakai; Zhai, Meiling; Fan, Hongxia; Ding, Lin (Frontiers in Psychology, 2025)
IntroductionAgainst the backdrop of global aging and the enduring impact of the COVID-19 pandemic, mental health issues among older adults have become increasingly prominent. This study aimed to investigate the effects of standardized 24-form simplified Tai Chi training on emotional regulation efficacy and subjective wellbeing in older adults and to verify the mediating role of emotional regulation efficacy between Tai Chi practice and subjective wellbeing.MethodsThe study was conducted in Zhengzhou, China, in autumn 2023. Sixty healthy older adults were randomly assigned to either an experimental group receiving Tai Chi training or a control group maintaining their regular lifestyle. At baseline, both groups were assessed using the Emotional Regulation Efficacy Scale and the Subjective Wellbeing Scale. The experimental group underwent an 8-week Tai Chi program, consisting of five 30-minute sessions per week under professional guidance, while the control group remained unchanged. Post-intervention, all variables were reassessed.ResultsThe results indicated significant improvements in emotional regulation efficacy (23.60 ± 2.33 to 26.60 ± 3.10, p < 0.001, Cohen’s d = 1.29), positive affect (27.53 ± 2.46 to 29.43 ± 3.12, p < 0.001, Cohen’s d = 0.77), negative affect (30.70 ± 2.90 to 32.13 ± 3.05, p = 0.002, Cohen’s d = 0.49), and subjective wellbeing (58.23 ± 5.29 to 61.57 ± 5.04, p = 0.000, Cohen’s d = 0.63) in the experimental group compared to baseline, with no significant changes observed in the control group. Between-group comparisons further confirmed the experimental group’s superior improvements across all measured variables. Mediation analysis demonstrated that Tai Chi’s benefits on wellbeing operated through dual pathways: while 83.8% of its total effect on subjective wellbeing was direct, 16.20% [β = 0.637, 95% CI (0.002, 1.731)] was mediated via enhanced emotional regulation efficacy. Notably, 22.27% of Tai Chi’s reduction in negative affect [β = 0.334, 95% CI (0.005, 0.761)] was attributable to this mediating mechanism, whereas no mediation was observed for positive affect—highlighting that Tai Chi’s promotion of positive emotions depends entirely on direct effects.DiscussionThese findings underscore Tai Chi’s unique capacity to both directly enhance wellbeing and empower older adults to manage negative emotions through improved emotional regulation. To translate these findings into practice, community health programs should integrate Tai Chi as a low-cost, accessible intervention for older adults, particularly those experiencing psychological stress or chronic conditions.